Changing socioeconomic inequalities in cancer incidence and mortality: Cohort study with 54 million person‐years follow‐up 1981–2011. Issue 6 (15th March 2017) - Teng, Andrea M.; Atkinson, June; Disney, George; Wilson, Nick; Blakely, Tony
Abstract : Cancer is increasingly responsible for the mortality gap between high and low socioeconomic position groups in high‐income countries. This study investigates which cancers are contributing more to socioeconomic gaps in mortality and how this changes over time.New Zealand census data from 1981, 1986, 1991, 1996, 2001 and 2006, were linked to three to five years of subsequent mortality and cancer registrations, resulting in 54 and 42 million years of follow‐up cancer incidence and mortality, respectively. Age‐ and ethnicity‐standardised cancer mortality rates and the slope index of inequality (SII) by income were calculated.The contribution of cancer to absolute inequalities (SII) in mortality increased from 16 to 27% for men and from 12 to 31% for women from 1981–84 to 2006–11, peaking in 1991–94 for men and in 1996–99 for women and then levelling off, parallel to peaks in lung cancer inequalities. Lung cancer was the largest driver of cancer inequality trends (49% of the cancer mortality gap in 1981–84 to 33% in 2006–11 for men and 32 to 33% for women) followed by colorectal cancer in men (2 to 11%) and breast cancer in women (declining from 44 to 13%). Women in the lowest income quintile experienced no decline in cancer mortality.The contribution of cancer to income inequalities in all‐cause mortality has expanded in this high‐income country. Action to address socioeconomic inequalities should prioritise equitable tobacco control, obesity control and improved access to cancer screening, early diagnosis and high quality treatment for those with the lowest incomes. Abstract : What's new? In high‐income countries, cancer is a major factor in the mortality gap between persons of low and high socioeconomic position. Few studies, however, have compared socioeconomic mortality gaps for specific cancers in the 2000s with previous decades. This analysis, using data from New Zealand, shows an increase in cancer mortality inequalities (by income) until the 1990s. Inequalities leveled off in the 2000s. Lung cancer accounted for a significant portion of the mortality gap, followed by colorectal cancer in men and breast cancer in women. Colorectal cancer mortality rates were highest in low‐income groups, while breast cancer mortality declined across income groups.